Prospects for yeast using in secondary dairy raw materials processing - T. V. Nersesyan; I. K. Kulikova; A. D. Lodygin (Современная наука и инновации)
The relevance of different types of yeasts application for synthesis of various types of commercially available products is substantiated. Directions of secondary dairy raw materials processing based on lactose biotransformation is analyzed. The possibility of using yeast, which is not capable of hydrolyzing lactose, for the purpose of recycling secondary milk raw materials has been shown.